Numerical Analysis of Natural Gas Delivery Discrepancy - Seleznev, Vadim (Journal of Informatics and Mathematical Sciences, 2012)
The article describes algorithm for optimization of discrepancies in natural gas supply to consumers. Numerical monitoring makes it possible to obtain computational estimates of actual gas deliveries over given time spans and to estimate their difference from corresponding values reported by gas consumers. Mathematical analysis of the discrepancy is based on a statement and numerical solution of identification problem of a physically proved gas dynamics mode of natural gas transmission through specified gas distribution networks. The identified mode parameters should have a minimum discrepancy with field measurements of gas transport at specified reference points of the simulated pipeline network.